Studi Literatur: Hubungan Mandi Malam dengan Penyakit Rematik pada Lansia - Shandra, Bebby; Dwinova, Keira; Amelia, Cynthia; Ariyanto, Januar (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that commonly affects the elderly. It is characterized by joint inflammation that causes pain, stiffness, and limited mobility. In many communities, there is a strong belief that night bathing may trigger or worsen rheumatic symptoms, especially in older adults. This study aims to identify and analyze public perceptions regarding night bathing and its relationship with the incidence of RA in the elderly. The method used is a literature review of scientific articles obtained from databases such as Google Scholar, PubMed, Garuda, and ScienceDirect, with publication criteria from 2020 to 2025 and relevance to the topic. The results show that night bathing is not scientifically proven to be a direct cause of rheumatoid arthritis. However, in elderly individuals who already experience RA symptoms, bathing at night with cold water may worsen joint pain. Misconceptions about this belief remain prevalent in society and can influence bathing habits and health decisions among the elderly. Proper education based on scientific evidence is needed to improve public understanding of the real causes of RA and to help reduce the impact of persistent health myths.